Holocene Sedimentary Environment in HP1 Core at Duong Kinh, Haiphong - Thi Thu Cuc, Nguyen; Duong, Nguyen Thuy; Phuong, Nguyen Thi Minh; Dinh Lam, Doan; Van Loi, Vu; Thi Thuy, An; Thi Xuan, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 2DO - 10.25073/2588-1094/vnuees.4326, 2020)
Holocene environment change in Haiphong coastal area was reconstructed based on diatom and grain-size analysis in the HP1 core at Duong Kinh, Haiphong. 52 diatom species were identified and divided in five diatom ecozones by changing of four diatom groups including marine planktonic, brackish planktonic, brackish benthic and freshwater one. The sedimentary environment at the Haiphong coastal area was estuary- bay condition in the Flandrian trangression (Z 1 , Z 2 and Z 3 Unit). Deltaic environment changed from prodelta (Z 4 ), delta front (Z 5 ) to delta plain (Z 6 and Z 7 ) corresponding to the Flandrian regression.